2014
DOI: 10.5326/jaaha-ms-5958
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Combination Therapy with Doxorubicin and Noncytotoxic Suramin in Dogs with Appendicular Osteosarcoma

Abstract: Although conventional treatment of dogs with osteosarcoma (OSA) by amputation and chemotherapy results in reported survival times (STs) of 262-413 days, no major improvements in STs have occurred in the past 2 decades. Suramin is a polysulfonated napthylurea, which at noncytotoxic concentrations in vitro, increases tumor sensitivity to chemotherapy, including doxorubicin. The study authors evaluated the combination of noncytotoxic suramin and doxorubicin after amputation in dogs with OSA. The hypothesis was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…Authors evaluated the combination of noncytotoxic suramin and doxorubicin after amputation in dogs with OSA. In conclusion of this experiment similar results to monotherapy median disease free time was achieved (Alvarez et al 2014 ). Also Kurzman and associates ( 1995 ) showed that benefits of adding Liposome-encapsulated Muramyl Tripeptyde to standard chemotherapy treatment (with cisplatin) and surgery is time.…”
Section: Treatmentsupporting
confidence: 86%
“…Authors evaluated the combination of noncytotoxic suramin and doxorubicin after amputation in dogs with OSA. In conclusion of this experiment similar results to monotherapy median disease free time was achieved (Alvarez et al 2014 ). Also Kurzman and associates ( 1995 ) showed that benefits of adding Liposome-encapsulated Muramyl Tripeptyde to standard chemotherapy treatment (with cisplatin) and surgery is time.…”
Section: Treatmentsupporting
confidence: 86%
“…However there is evidence suggesting six doses of carboplatin may be superior to alternating doxorubicin and carboplatin regimens [ 53 ]. In canine OSA adjuvant chemotherapy with either doxorubicin or the platinum-based compounds including cisplatin and carboplatin have been associated with increased survival times over amputation alone [ 54 57 ]. The relative merits of the individual chemotherapy drugs have been evaluated.…”
Section: Treatment Of Osteosarcoma In Humans and Dogsmentioning
confidence: 99%
“…Characterized by high malignant potential and invasive ability, osteosarcoma, a common tumor in adolescents, exhibits lung metastasis at an early stage (19). Consequently, it is associated with a poor prognosis and a low survival rate.…”
Section: Discussionmentioning
confidence: 99%